A Molecular Approach to Explore the Background Benthic Fauna Around a Hydrothermal Vent and Their Larvae: Implications for Future Mining of Deep-Sea SMS Deposits - Klunder, Lise; de Stigter, Henko; Lavaleye, Marc S. S.; van Bleijswijk, Judith D. L.; van der Veer, Henk W.; Reichart, Gert-Jan; Duineveld, Gerard C. A. (Frontiers in Marine Science, 2020)
Seafloor massive sulfide (SMS) deposites are commonly found at hydrothermal vents and recently gained the special interest of mining industries. These deposits contain valuable metals and methods are currently developed to mine deep sea SMS deposites. However, excavation of SMS deposits potentially pose a threat to benthic life at the mining site itself, and also in the surrounding environment with plumes of suspended sediment and fine-grained SMS debris created during deep sea mining activities being highlighted as one of the major threats to deep-sea benthic fauna. The benthic communities surrounding the vents are, however, poorly known. As they are often exposed to natural plumes studying such communities could provide valuable information on their resilience towards mining related plumes. The Rainbow hydrothermal vent site at the Mid-Atlantic Ridge is a site characterized by one of the largest continuous natural plumes, which is found persisting over an extensive area. Sediment and water samples were taken both upstream and downstream of the Rainbow hydrothermal vent. Approximately 25km away from the vent reference sites were samples as well. In addition to detecting the plume itself, concentrations of major and trace-metals in the sediments were used as tracers for long time sustained plume influence. At all sites we assessed benthic species composition and detected larvae. Metabarcoding methods were used to determine species composition. Benthic species composition in the sediment was shown to differ between all locations and was highly influenced by the plume’s fall out. Arthropoda were more dominant closer to the vent whereas Annelida and Nematoda were more dominant at the reference locations. Conservation and restoration of all these communities after a deep sea mining event will be difficult due to the spatial variation of these benthic communities.